The Effect of WC-17Co Thermal Spray Coating By HVOF and Hard Chromium Electroplating on the Fatigue Life and Abrasive Wear Resistance of AISI 4340 High Strength Steel - Souza, Renato C.; Nascimento, Marcelino P. [UNESP]; Voorwald, Herman J.C. [UNESP]; Pigatin, Walter L. (De Gruyter, 2003)
One of the most interesting alternatives for replacement of hard chrome plating is tungsten carbide thermal spray coating applied by the high velocity oxy-fuel (HVOF) process which presents a safer, cleaner and less expensive alternative to chromium plating. The objective of this research is to compare the influence of the tungsten carbide-17cobalt (WC-17Co) coating applied by high velocity oxy fuel (HVOF) process with that of hard-chromium electroplating on the fatigue strength and abrasive wear of AISI 4340 steel. © 2003, by Walter de Gruyter GmbH & Co. All rights reserved.
Keywords: abrasive wear; fatigue; hard chromium electroplating; HVOF; WC-17Co thermal spray coating